Dendroenergetic potential of two clones of Eucalyptus sp. in Corrientes, Argentina - Maggio, Alejandro Daniel; Caniza, Federico Javier; Cellini, Juan Manuel; Martinez-Meier, Alejandro (Instituto de Ecología, A.C., 2022)
Forest plantations for energy purposes are aimed at obtaining large amounts of biomass through short-term rotations. The aim of this work was to study the dendroenergetic potential of two clones of Eucalyptus sp. growing in the hills and sandy plains of Corrientes, Argentina. The relationships between biomass productivity and forestry, climatic and environmental variables were analysed. Survival and productivity in volume were high. Significant differences were recorded between the clones evaluated for biomass production based on their compartments and age. At 24 months, the stem biomass production for a management scheme of 3333 ha-1 trees was 32,245 Mg ha-1 and 38,543 Mg ha-1 of the pure and hybrid clone, respectively. In a context of lack of limitations, from the climatic point of view and site conditions, the annual biomass productivity can be associated with the planting density. In low-fertile fertile soils, both clones register high productivity in high planting densities schemes. The promotion of the generation of renewable energies from forest biomass is an opportunity for Corrientes, since it has the resource and favorable climatic conditions, although it is necessary to continue studying the development of these systems in fragile environments, identifying management practices that reduce their impact and favor sustainable management.